Be loud! Esperienze di maternità afroitaliana, tra nerezza, radicalità e spazi di cittadinanza affettiva - Scarabello, Serena (Antropologia Pubblica, 2024)
This article explores the intertwining of maternal and citizenship practices, focusing on the experiences of Afro-descendant Italian mothers and on the meanings that blackness can take on in educational relationships and against the backdrop of hegemonic and colour-blind notions of Italianness. By approaching motherhood as a biosocial threshold, it analyses the process through which mothers seek a “good balance” in supporting the building of self-esteem and pride in their sons and daughters, while transmitting to them the political value of the colour-line, awareness of the social hierarchies associated with it and the different ways in which it is articulated in social life. Furthermore, by highlighting the lines of continuity and discontinuity traced with the parental styles adopted by the previous generation, this contribution aims to reflect on the meaning of the “radical relationality” introduced by black Italian mothers in the social spheres, understanding it not as a breaking choice, but rather as a way to expand and diversify the spaces of affective citizenship for themselves and their descendants.